artikel Manajemen Pendidikan Anak Usia Dini pada Paud Purwanida Metro - Azizah, Hanifah Fitria (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
This study uses a qualitative and descriptive approach. The research subjects were managers, educators, students, and parents selected using purposive sampling technique. Data was collected through observation, interviews, and documentation. The validity of the data is done through the persistence of observation, participation, and adequacy of references. The results showed that the management of the PAUD Purwanida program was structured according to the vision and mission of the institution by carrying out management functions including; planning, implementation, supervision and development. Planning of educational activityprograms by compiling activity plans according to the provisions including planning for administration, teaching, teachers, and curriculum, involving teachers and the community. Managers as leaders in carryingout management functions emphasize cooperation based on sincerity, enthusiasm, and high loyalty. Planning is done by strategic planning, preparing lesson plans starting from yearly, semester, monthly, weekly to daily.The implementation of education is directed at the learning process, the principal's efforts encourage teachers to apply creative and varied learning strategies. The general form of the organization has reflected a relevance between the capabilities and skills of personnel with educational needs, and organizing humanresources for institutional learning activities. Organizing is done by coordinating tasks, opportunities, experiences and insights with open communication, holding regular meetings to discuss efforts to improve performance. Supervision of early childhood education activities is carried out with direct supervisory supervision carried out by the principal and functional supervision is carried out by supervisors. Supervision is carried out by direct observation, through supervision, regular meetings with educators. Collaboration is carried out with parents, through monthly meetings (parenting), and partners related to PAUD. Assessmentand evaluation is done by giving assignments, observations, diaries, anecdotes, performance, work results, and educational visits.